2008
DOI: 10.1097/cej.0b013e3282b6fd78
|View full text |Cite
|
Sign up to set email alerts
|

Occupational physical activity and risk for cancer of the colon and rectum in Sweden among men and women by anatomic subsite

Abstract: BACKGROUND-The inverse association between physical activity and colon cancer is well established, at least in men. We investigated the association of occupational physical activity with subsite-specific colorectal cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 50 publications
(60 reference statements)
4
42
1
Order By: Relevance
“…In this study the protective effect in men seemed a bit more pronounced than in women (24% versus 21%) when the two genders were compared. It was also observed in this study that physical activity also reduced the risk of rectal cancer, but the effect was not as strong as that in colon cancer [4,5]. Moreover; reduced incidence of colon cancer was observed in professionals that required continuous daily physical activity.…”
Section: Introductionsupporting
confidence: 48%
“…In this study the protective effect in men seemed a bit more pronounced than in women (24% versus 21%) when the two genders were compared. It was also observed in this study that physical activity also reduced the risk of rectal cancer, but the effect was not as strong as that in colon cancer [4,5]. Moreover; reduced incidence of colon cancer was observed in professionals that required continuous daily physical activity.…”
Section: Introductionsupporting
confidence: 48%
“…Among the dose -response effects evaluated, less than half reported a significant trend. Of note, several studies that examined dose -response effects in men and women separately found significant trends only in men (Chao et al, 2004;Lee et al, 2007;Takahashi et al, 2007;Howard et al, 2008;Nilsen et al, 2008), but one found significant trends only in women (Thune and Lund, 1996) and two in both men and women (Wei et al, 2004;Moradi et al, 2008). In contrast, only 10 case-control studies reported a test for trend, and four found significant results for at least one group.…”
Section: Discussionmentioning
confidence: 87%
“…47,48 Physical inactivity is associated with a rather small increase in colon but not rectal cancer risk. 49,50 Although there has been an increase in the total meat intake per capita in the United States since the 1970s, red meat consumption appears to have decreased slightly, but there is no evidence of a particular subsite-specific effect. 35,51 Overall, obesity, diabetes, and physical inactivity have increased over time and would tend to increase the risk of CRC in the population, with a greater increase expected in the colon than in the rectum in the absence of other factors.…”
Section: Discussionmentioning
confidence: 96%